Controllable wide temperature range and high damping polyurethane elastomer based on disulfide bond and dangling chain. (5th March 2021) - Xiaolin, Jiang; Rui, Qin; Minhui, Wang; Min, Xu; Yeming, Sheng; Xun, Lu
Abstract: Aiming at the common problems of weak controllability of damping temperature range and poor mechanical properties in damping elastomer materials. Herein, we design a polyurethane‐containing dynamic disulfide bonds and dangling chains to address this dilemma. The as‐prepared polyurethane exhibits an unprecedented damping range of 182°C (−62 to 120°C), and the tensile strength reaches 6.8 MPa, which is at the forefront of the same type of research. We innovatively introduce aromatic disulfides to the system, in which disulfide bonds can be spontaneously exchanged dynamically at room temperature, making the damping performance of the elastomer above room temperature improved, and a small amount of hydroxyl‐terminated polydimethylsiloxane (OH‐PDMS) is used as a dangling chain to promote the damping property of the elastomer between the glass transition temperature and room temperature. The synergistic effect of disulfide bonds and dangling chains makes the controllability of polyurethane damping temperature range realized. Furthermore, polyurethane elastomer is equipped with good thermal stability duo to the introduction of OH‐PDMS. And, the high‐performance polyurethane elastomer has great potential in practical application.